Are Conservatives Really More Simple‐Minded than Liberals? The Domain Specificity of Complex Thinking. Issue 6 (16th October 2015) - Conway, Lucian Gideon; Gornick, Laura Janelle; Houck, Shannon C.; Anderson, Christopher; Stockert, Jennifer; Sessoms, Diana; McCue, Kevin
Abstract : Prior research suggests that liberals are more complex than conservatives. However, it may be that liberals are not more complex in general, but rather only more complex on certain topic domains (while conservatives are more complex in other domains). Four studies (comprised of over 2, 500 participants) evaluated this idea. Study 1 involves the domain specificity of a self‐report questionnaire related to complexity (dogmatism). By making only small adjustments to a popularly used dogmatism scale, results show that liberals can be significantly more dogmatic if a liberal domain is made salient. Studies 2–4 involve the domain specificity of integrative complexity. A large number of open‐ended responses from college students (Studies 2 and 3) and candidates in the 2004 Presidential election (Study 4) across an array of topic domains reveals little or no main effect of political ideology on integrative complexity, but rather topic domain by ideology interactions. Liberals are higher in complexity on some topics, but conservatives are higher on others. Overall, this large dataset calls into question the typical interpretation that conservatives are less complex than liberals in a domain‐general way.